Expanding the Phenotype of the CACNA1C-Associated Neurological Disorders in Children: Systematic Literature Review and Description of a Novel Mutation - Lorenzo Cipriano; Raffaele Piscopo; Chiara Aiello; Antonio Novelli; Achille Iolascon; Carmelo Piscopo (MDPI AG, 2024)
Background: CACNA1C gene encodes the alpha 1 subunit of the CaV1.2 L-type Ca2+ channel. Pathogenic variants in this gene have been associated with cardiac rhythm disorders such as long QT syndrome, Brugada syndrome and Timothy syndrome. Recent evidence has suggested the possible association between CACNA1C mutations and neurologically-isolated (in absence of cardiac involvement) phenotypes in children, giving birth to a wider spectrum of CACNA1C-related clinical presentations. However, to date, little is known about the variety of both neurological and non-neurological signs/symptoms in the neurologically-predominant phenotypes. Methods and Results: We conducted a systematic review of neurologically-predominant presentations without cardiac conduction defects, associated with CACNA1C mutations. We also reported a novel de novo missense pathogenic variant in the CACNA1C gene of a children patient presenting with constructional, dressing and oro-buccal apraxia associated with behavioral abnormalities, mild intellectual disability, dental anomalies, gingival hyperplasia and mild musculoskeletal defects, without cardiac conduction defects. Conclusions: The present study highlights the importance of considering the investigation of the CACNA1C gene in children's neurological isolated syndromes, and expands the phenotype of the CACNA1C related conditions. In addition, the present study highlights that, even in absence of cardiac conduction defects, nuanced clinical manifestations of the Timothy syndrome (e.g., dental and gingival defects) could be found. These findings suggest the high variable expressivity of the CACNA1C gene and remark that the absence of cardiac involvement should not mislead the diagnosis of a CACNA1C related disorder.